Isolation and characterization of thermophilic, alkaliphilic, cellulose‐degrading bacillus thermoalcaliphilus sp. nov. from termite (odontotermes obesus) mound soil of a semiarid area - Sarkar A. (My University, 2025)
A new heterotrophic, thermophilic, alkaliphilic, facultatively anaerobic, cellulose‐degrading bacterium strain STS1 was isolated from mound soils infested with the higher termite Odontotermes obesus in the semiarid ecosystem of Delhi (India). The gram‐positive, spore‐forming, catalase‐positive Bacillus sp. grew on natural and raw celluloses. The taxonomic position of the organism was investigated. The guanine plus cytosine content of the isolate was found to be 48.6 mol% (melting temperature profile). Addition of peptone or yeast extract stimulated growth. The isolate did not grow on silica gel plates or on agar media in which the agar was the sole source of carbon and energy. The high growth temperature of 70°C and the pH of 9.0 are characteristic of this species. The role of this bacterium in the semiarid ecosystem is discussed. Because of its high optimum temperature and high optimum pH for growth, the name Bacillus thermoalcaliphilus is proposed. © 1991 Taylor & Francis Group, LLC.